Primigravida dengan hiperemesis gravidarum + kista ovari - Diar Muhammad Haerulloh; Fonda Octarianingsih Shariff (THE JOURNAL OF Mother and Child Health Concerns, 2025)
A 28-year-old patient came to the emergency room of Bintang Amin Hospital with complaints of vomiting approximately 6 times since noon accompanied by nausea. The patient said that abdominal pain was like cramps from 2 hours of SMRS and lately had no appetite due to nausea. Blood pressure 110/75 mmHg, pulse rate 94 x/min, respiratory rate 20x/min, temperature 36.2 °C, oxygen saturation 99%. In the abdominal palpation examination, suprapubic (+) pressure pain was obtained. In the hematological support examination, a decrease in hemoglobin was obtained by 11.1 g/dl, a decrease in hematocrit by 31%, a decrease in MCV of 79 fl, an increase in leukocytes of 23,000 ul and in a complete urine examination, leukocytes H+/(75), Protein H+/(50), ketones HH++++/(150), urobilinogen +/(2) were obtained. Ultrasound examination was obtained D:9.50, D:4.68, GS: not yet visible. The diagnosis in this case is primigravida with hyperemesis gravidarum + ovarian cyst. The management obtained by the patient is observation of complaints, IVFD RL + 1amp neurobion gtt 20 3, pronalges supp, inj ondansetron 2x1 amp, paracetamol 3x500mg. The prognosis in this patient is dubia ad bonam. Keywords: HEG; Ovarian Cysts; Vomiting. Pasien usia 28 tahun datang ke IGD Rumah Sakit Bintang Amin dengan keluhan muntah kurang lebih 6x sejak siang disertai mual. Pasien mengatakan nyeri perut seperti keram dari 2 jam SMRS dan akhir akhir ini tidak nafsu makan karna mual. Tekanan darah 110/75 mmHg, denyut nadi 94 x/menit, laju pernapasan 20x/menit, suhu 36,2 °C, saturasi oksigen 99%. Pada pemeriksaan abdomen palpasi didapatkan nyeri tekan (+) suprapubik. Pada pemeriksaan penunjang hematologi didapatkan penurunan hemoglobin dengan 11,1 g/dl, penurunan hematokrit 31 %, penurunan MCV 79 fl, peningkatan leukosit 23.000 ul dan pada pemeriksaan urin lengkap didapatkan leukosit H+/(75), Protein H+/(50), keton HH++++/(150), urobilinogen +/(2). Pemeriksaan USG didapatkan D:9.50, D:4.68, GS:belum tampak. Diagnosis pada kasus ini yaitu primigravida dengan hiperemesis gravidarum+kista ovari. Tatalaksana yang didapat oleh pasien yaitu observasi keluhan, IVFD RL + 1amp neurobion gtt 20 3, pronalges supp, inj ondansetron 2x1 amp, paracetamol 3x500mg. Prognosis pada pasien ini yaitu dubia ad bonam. Kata Kunci: HEG; Muntah; Kista Ovari.